Correlated expansions of n 1 S and n 3 S states for two-electron atoms in exponential cosine screened potentials - Ancarani, L. U. (2014)
Two–electron atoms embedded in a plasma environment are studied with screened and exponential cosine screened Coulomb model potentials. Within a configuration interaction approach, and using parameter–free explicitly correlated basis functions, we have calculated the ground-state and first excited-state energies (and other mean values) for H−, He, and Li+. We analyze their evolution with the screening parameter and provide simple fits, which allow for practical and rapid evaluations for example in plasma applications.